A Commentary on “A Comparison Between Two Different Definitions of Contrast-Associated Acute Kidney Injury for Long-Term Mortality in Patients with Chronic Kidney Disease Undergoing Coronary Angiography” [Letter] - Xu J; Ye L (Clinical Interventions in Aging)
Jiawei Xu, Lu Ye The Third Affiliated Hospital of Zhejiang, Chinese Medical University, Hangzhou, Zhejiang, People’s Republic of ChinaCorrespondence: Lu Ye, The Third Affiliated Hospital of Zhejiang, Chinese Medical University, Hangzhou, Zhejiang, 310009, People’s Republic of China, Email 59843771@qq.com